2014
DOI: 10.1098/rsif.2013.1108
|View full text |Cite
|
Sign up to set email alerts
|

Competition, virulence, host body mass and the diversification of macro-parasites

Abstract: Adaptive speciation has been much debated in recent years, with a strong emphasis on how competition can lead to the diversification of ecological and sexual traits. Surprisingly, little attention has been paid to this evolutionary process to explain intrahost diversification of parasites. We expanded the theory of competitive speciation to look at the effect of key features of the parasite lifestyle, namely fragmentation, aggregation and virulence, on the conditions and rate of sympatric speciation under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 119 publications
(183 reference statements)
0
4
0
Order By: Relevance
“…Aggregation of parasites amongst hosts is one of the rare phenomena in biology that has been described as a ‘law’ [ 1 , 5 ]. The negative binomial distribution has been of central importance to establish evidence for aggregation in data [ 5 , 42 ], as well as to provide theoretical predictions on ecological and evolutionary consequences of parasite distributions among hosts [ 6 , 9 , 43 ]. However, a good fit to a negative binomial distribution does not provide any information about the causes of aggregation since a number of different biological phenomena have been proposed to generate this flexible distribution [ 44 ], as well as different combinations of statistical laws [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregation of parasites amongst hosts is one of the rare phenomena in biology that has been described as a ‘law’ [ 1 , 5 ]. The negative binomial distribution has been of central importance to establish evidence for aggregation in data [ 5 , 42 ], as well as to provide theoretical predictions on ecological and evolutionary consequences of parasite distributions among hosts [ 6 , 9 , 43 ]. However, a good fit to a negative binomial distribution does not provide any information about the causes of aggregation since a number of different biological phenomena have been proposed to generate this flexible distribution [ 44 ], as well as different combinations of statistical laws [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation has been shown to affect parasite ecology by stabilizing host-parasite population dynamics [ 6 , 7 ] and facilitating interspecific co-infection as a result of increased host susceptibility [ 8 ]. Aggregation also influences parasite evolution by, e.g., increasing the level of intra-specific competitive interaction and the rate of within-host adaptive parasite diversification [ 9 ]. Accordingly, aggregation of parasites amongst hosts affects the transmission of infectious human diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stability of parasite-host interactions is thought to be dependent on the degree of parasite aggregation (Anderson and May 1978;Anderson and Gordon 1982). Parasite aggregation among hosts can also either increase (Cornell et al 2003) or decrease (Rascalou and Gourbière 2014) the rate of parasite adaptive evolution. Taken collectively, aggregation of infective stages of parasites in the environment might have an obvious cause and an important consequence that helps explain other phenomenon well described in parasitehost study systems.…”
Section: Discussionmentioning
confidence: 99%
“…Models on plant parasites, for instance, have indicated that evolutionary divergence of parasite phenotypes can be driven by seasonal transmission and associated fitness trade-offs (Hamelin et al, 2011), such as may also occur with annual treatments and reduced density-dependent factors. One such recent model describes how competition explains intra-host diversification of parasites (Rascalou and Gourbiere, 2014). They show that parasite adaptive evolution is faster in highly fragments parasites populations and for weakly aggregated and virulent parasites, all factors which could be affected by drug selective pressures, hybridizations and associated trade-offs.…”
Section: Elucidating the Potential Role Of Hybridisation And Introgrementioning
confidence: 99%